Optimalisasi Alat Gali-Muat Dan Alat Angkut Terhadap Produksi Overburden Dengan Metode Kapasitas Produksi Dan Metode Antrian Di Pit Timur Periode Agustus 2017 PT. Artamulia Tata Pratama, Site Tanjung Belit, Bungo, Jambi - Yuli Asri; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. In the mining process, the availability of dump truck equipment and loading equipment will determine the sustainability of production which has an impact on productivity and efficiency. The purpose of this study is to optimize production on stripping the overburden using the queuing method, match factor. The location of the study was conducted at PT. Artamulia Tata Pratama, Tanjung Belit, site Bungo, Jambi in August 2017 – September 2017. The loading equipment used is the PC 1250 Komatsu Excavator and the Komatsu HD 465-7 dump truck. The simulation results of the number of dump trucks needed based on production capacity is 17 units while based on queuing theory there are 17 units. Where the actual dump trucks used were 19 unitsKeywords:   Production, queue, match factor, optimization of production, coal mining.